PENGARUH CSR DAN GCG TERHADAP NILAI PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014 - Elvina Embang (Parsimonia - Jurnal Ekonomi dan Bisnis, 2016)
The objective of this research is to finding out the influence of CSR and GCG on firm value for manufacture companies listed in Indonesia Stock Exchange. Previous studies have shown varying results. To obtain valid results, the testing performed on each variable based on the hypothesis constructed. CSR is measured by GRI index. Whereas, GCG is represented become two variable, they are: managerial ownership and institutional ownership. Indeed, the firm value is reprensented by Tobin’s Q index. Data collection is done by using purposive sampling of manufactur companies that listed on Indonesia Stock Exchange in 2010 until 2014. Eleven coal mining companies use as a sample. The analysis methods in this study use classical assumption test and multiple regression. The results of this study indicate that CSR has effect on the firm’s value, while the managerial ownership and institutional ownership in GCG variables has no affect the value of the company.